Pelatihan Optimasi Media Promosi Bagi Pengelola Desa Wisata Pulau Mubut - Yeni Rokhayati; Metta Santiputri; Sartikha Sartikha; Afdhol Dzikri; Mira Chandra Kirana; Supardianto Supardianto; Siskha Handayani; Dwi Amalia Purnamasari (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
Mubut Island needs to carry out promotional activities through social media, not only conventionally by word of mouth. This is done so that the Pulau Mubut Tourism Village is increasingly known and visited by many people. Considering the age of the managers and their activity, as well as the target of visitors from Mubut Island, it was decided that the promotional media that was optimized in 2022 was Facebook social media. Because in the future it will be the managers who will manage the promotional media for this Tourism Village, it is important to train these managers to be able and proficient in optimizing their Facebook social media. The training activities will be evaluated by measuring the managers's ability to optimize the Facebook media of Mubut Island. As a result, the managers was able to optimize the promotional activities of Mubut Island through social media Facebook, namely by looking at the manager's activity in posting and the increasing number followers.